Eat this, not that! : the best (& worst) foods in America - Zinczenko, David (Ballantine Books, 2019)
Did you know that if you're watching your waistline, a McDonald's Big Mac is better than a Five Guys Cheeseburger? Or that the health promise of the Cheesecake Factory's Grilled Chicken and Avocado Club is dubious? Or that when shopping for condiments, the real winner is Kraft mayo with olive oil instead of Hellman's “Real?” Reading ingredient labels and scrutinizing descriptions on menus is hard work, but with side-by-side calorie and nutrition comparisons and full-color photos on every page, Eat This, Not That! makes it easy! Diet guru Dave Zinczenko goes aisle-by-aisle through every major American staple<U+2014>from frozen foods, cereals, and sodas, to the dairy cases, international foods, and the produce aisle<U+2014>as well as every chain and fast food restaurant in the country to pick the winners and losers. You'll find more than 1,250 slimming and often surprising swaps, a helpful list of the “worst foods in America” by category, plus testimonials from real people who lost weight simply by consulting Zinczenko's easy-to-follow advice. Now the book that changed the way Americans choose meal ingredients, food brands, and menu options is completely updated<U+2014>and it'll help satisfy both the appetite and diet goals of even the hungriest reader!